Pedagogias decoloniais e professores de língua portuguesa: a desconstrução da história única na escola - Legramandi, Aline Belle (2023)
The object of this research is the coloniality and anticoloniality of pedagogical practice and has as its central question: what are the conceptions of Portuguese language teachers regarding an anticolonial pedagogical practice? The general objective is to analyze the conceptions of Portuguese language teachers regarding an anticolonial pedagogical practice. From this question, three others arise: 1) what are the conceptions of Portuguese language teachers regarding an anticolonial practice?; 2) what knowledge do Portuguese language teachers have about colonial pedagogical practices?; and 3) do teachers identify the reproduction of hegemonic culture and knowledge in their pedagogical practices? The general objective is to analyze the conceptions of Portuguese language teachers regarding an anticolonial pedagogical practice. The specific objectives are: a) To identify in the conceptions of Portuguese language teachers an anticolonial pedagogical practice; b) To identify the knowledge that Portuguese language teachers have about colonial pedagogical practices; c) To verify if teachers identify the reproduction of hegemonic culture and knowledge in their pedagogical practices; d) To verify colonial practices carried out by Portuguese language teachers; and e) To verify anticolonial practices promoted by Portuguese language teachers. The theoretical framework, which engages historical-dialectical materialism with decolonial theories, was constructed in a way to adhere to the object to achieve the objectives described above, integrating the perspectives of Vera Maria Ferrão Candau, Zulma Palermo, Catherine Walsh, João Colares Mota Neto, Dermeval Saviani, and Paulo Freire, and serves as a support for the core category of this research, pedagogical practice. The methodology adopted is a mixed, quantitative-qualitative approach and used a questionnaire and semi-structured interviews as data collection instruments. Data were collected in legislation and documents that guide the pedagogical practice of Portuguese language teachers, in the responses given in the questionnaire by 278 high school Portuguese language teachers from the state public education system of São Paulo, and in the speeches of 6 Portuguese language teachers, also working in high school in the state public education system of São Paulo, which depict the conceptions of the interview subjects. To assist in the analysis and interpretation of data, we adopted Mikhail Bakhtin's discourse analysis technique.